ENHANCING VOCABULARY MASTERY OF THE TENTH GRADE STUDENTS OF SMA MUHAMMADIYAH 2 PALEMBANG THROUGH SUBTITLED MOVIES - Ibrahim, Wahid (Jurnal Dosen Universitas PGRI Palembang)
ABSTRAKThe objectives of this study were to find out whether or not the use of subtitledÂ movies could (1) enhance studentsâ vocabulary achievement; and (2) difference in the tenthÂ gradersâ vocabulary achievement between who were though by using subtitled movies andÂ those who were not. The sample of the study was all tenth grade students of SMAÂ Muhammmadiyah 2 Palembang in the academic year of 2013/2014 that consisted of 71Â students. A quasi-experimental design was used in this research with 20 meetings includingÂ pre-test and post-tests. The findings showed that (1) there was a significant difference in thetenth gradersâ vocabulary mastery after they are taught using subtitled movie. (2) UsingÂ subtitled movie as a medium could enhance vocabulary mastery. (3) Using subtitled movie orÂ audio visual as medium to teach English provide the students more fun in teaching learningactivity. To show the value of the results of this research, some interpretations are presentedÂ and conclusions are drawn.Key Words: Subtitled Movies, Vocabulary Mastery